Prevalence and Associated Factors of Malocclusion among Preschool Children in Huizhou, China: A Cross-Sectional Study - Lin, Lude; Chen, Wanting; Zhong, Dejun; Cai, Xiayuan; Chen, Jieyi; Huang, Fang (Healthcare (Basel), 2023)
This survey examined the prevalence of malocclusion and its associated factors in 3- to 5-year-old children in Huizhou, China. Children were recruited from 21 kindergartens using a multistage sampling method. Two examiners performed oral examinations on the children, assessing occlusal traits, including primary molar and canine relationship, overjet, crossbite, overbite, anterior open bite, scissor bite, midline deviation, crowding, and spacing. Caries experience was recorded. Self-administered questionnaires were distributed to collect background information and oral health-related habits. Chi-square test, Mann–Whitney U test, and binary logistic regression were conducted. The study invited 1485 children and eventually recruited 1454 (52.9% boys; response rate: 97.9%). The prevalence of malocclusion was 68.3%, and deep overbite was found in 48.6% of the children. Children who had lip-biting habits had a higher prevalence of deep overbite than those who did not (OR = 2.36, p < 0.05). Children who had digit-sucking habits and dental caries in anterior maxillary teeth had a lower prevalence of deep overbite than those who did not (OR = 0.73 and 0.70, respectively, p < 0.05). In conclusion, over half of the children in Huizhou who participated in the study had malocclusion. Dental caries in anterior maxillary teeth, digit-sucking, and lip-biting were the associated factors of deep overbite.